2013
DOI: 10.1103/physreva.87.023615
|View full text |Cite
|
Sign up to set email alerts
|

Lattice Monte Carlo calculations for unitary fermions in a finite box

Abstract: We perform lattice Monte Carlo simulations for up to 66 unitary fermions in a finite box using a highly improved lattice action for nonrelativistic spin 1/2 fermions. We obtain a value of 0.366 +0.016 −0.011 for the Bertsch parameter, defined as the energy of the unitary Fermi gas measured in units of the free gas energy in the thermodynamic limit. In addition, for up to four unitary fermions, we compute the spectrum of the lattice theory by exact diagonalization of the transfer matrix projected onto irreducib… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
60
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 66 publications
6
60
0
Order By: Relevance
“…This agreement is insensitive to the form of the extrapolation used, as the Hadron Spectrum σ-meson mass result at m π ∼ 391 MeV is itself less that one standard deviation smaller than the best-fit nucleon excitation scale. Fits where δE = M σ is explicitly assumed can be performed more precisely and lead to consistent results with smaller uncertainties for the nucleon mass M N = 0.7226 (18), as shown in Fig. 35.…”
Section: An Improved Estimatormentioning
confidence: 91%
See 1 more Smart Citation
“…This agreement is insensitive to the form of the extrapolation used, as the Hadron Spectrum σ-meson mass result at m π ∼ 391 MeV is itself less that one standard deviation smaller than the best-fit nucleon excitation scale. Fits where δE = M σ is explicitly assumed can be performed more precisely and lead to consistent results with smaller uncertainties for the nucleon mass M N = 0.7226 (18), as shown in Fig. 35.…”
Section: An Improved Estimatormentioning
confidence: 91%
“…They presented general arguments, that are discussed below, suggesting that this behavior might be a generic feature of quantum field theories. Knowledge of the approximate form of the correlation function distribution was exploited to construct an improved estimator, the cumulant expansion, that was productively applied to subsequent studies of unitary fermions [15][16][17][18]. Correlation function distributions have been studied analytically in the Nambu-Jona-Lasinio model [13,19], where it was found that real correlation functions were approximately log-normal but complex correlation functions in a physically equivalent formulation of the theory were broad and symmetric at large times with qualitative similarities to the QCD nucleon distribution.…”
Section: Introductionmentioning
confidence: 99%
“…It is suitable for studying hadronic physics as well as atomic physics in a finite volume (see Refs. [66,67] for examples of the Lüscher method applied on atomic systems).…”
Section: Introductionmentioning
confidence: 99%
“…An example is seen in the evolution [10] of the determination of the so-called Bertsch parameter at unitarity. Quantitative comparisons have allowed validation of our understanding and provided an impetus for developments of both experimental and theoretical techniques.…”
mentioning
confidence: 99%